Music Congruity Effects on Product Memory, Perception, and Choice - North, A.; Sheridan, Lorraine; Areni, C. (Elsevier Ltd, 2015)
© 2015. Music congruity effects on consumer behavior are conceptualized in terms of cognitive priming of semantic networks in memory, and operationalized as congruent with a product's country of origin (Experiment 1), or congruent with the utilitarian (Experiment 2) or social identity (Experiments 2 and 3) connotations of a product. Hearing a specific genre of music (e.g., classical) activates related concepts in memory (e.g., expensive, sophisticated, formal, educated), which influences the memory for, perception of, and choice of products. Consistent with this account of music congruity effects, three laboratory experiments show that playing music of a specific genre during initial product exposure improved subsequent recall of conceptually related (i.e., congruent) products compared to unrelated products (Experiment 1), affected product choice in favor of congruent products (Experiment 1), and affected how much participants were willing to pay for congruent products (Experiments 2 and 3).